2000
DOI: 10.1002/1098-1071(2000)11:7<470::aid-hc5>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Long‐chain functional bisphosphonates: synthesis, anticalcification, and antiresorption activity

Abstract: FIGURE 1Structures of geminal bisphosphonates in clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Furthermore, the pair of enantiomers, 8 and 9, also show similar inhibition constants, in contrast to their differing inhibition constants on MMPs. 24 Finally, Table 1 also contains 1,4-butanebiscarbamoylphosphonic acid and its tetraethyl ester (compounds 10 and 11, respectively), 34 both of which show similar inhibition characteristics to the mono-CPO compounds mentioned above. Among the compounds in Table 1, an in-depth study was devoted to cyclopentyl-CPO (3, CPCPA), 23 which revealed significantly inhibited cellular invasion and capillary formation in vitro.…”
Section: ■ Resultsmentioning
confidence: 94%
“…Furthermore, the pair of enantiomers, 8 and 9, also show similar inhibition constants, in contrast to their differing inhibition constants on MMPs. 24 Finally, Table 1 also contains 1,4-butanebiscarbamoylphosphonic acid and its tetraethyl ester (compounds 10 and 11, respectively), 34 both of which show similar inhibition characteristics to the mono-CPO compounds mentioned above. Among the compounds in Table 1, an in-depth study was devoted to cyclopentyl-CPO (3, CPCPA), 23 which revealed significantly inhibited cellular invasion and capillary formation in vitro.…”
Section: ■ Resultsmentioning
confidence: 94%
“…mp 208-209 1C. NMR (D 2 O): 31 P, 10.2 ppm (q, J POCH = 9.7 Hz); Disodium ortho-(methylphosphonato)formylbenzoate (7). To a solution of compound 5 (60 mg) dissolved in D 2 O (0.4 mL) solid Na 2 CO 3 was added until pH 10.…”
Section: Discussionmentioning
confidence: 99%
“…4 The antiviral pyrophosphate analogs, phosphonoacetic and phosphonoformic acids have also been reported to accumulate in bone and teeth which detracts from their value as drugs. 5 In another approach, it was reported in previous papers from our laboratory that bisacylphosphonates 6 and to a lesser extent, other long-chain bisphosphonates 7 are also biologically active in calcium related disorders. X-Ray crystallographic results indicate that bisacylphosphonates interact with calcium ions to form polynuclear structures in which each terminus of the molecule is bound to a separate calcium ion, which is bound to additional bisacylphosphonates.…”
Section: Introductionmentioning
confidence: 99%
“…However, subsequent workers have found that alkyl halides do not always readily undergo displacement reactions with [(RO) 2 P(O)CF 2 ] - anions and that some of Obayashi's work is not reproducible at the published yields. The reported yields vary from 0% to 43% with simple primary alkyl iodides and bromides. , A recent work brings an example of the good-yielding reaction between [( i PrO) 2 P(O)CF 2 ] - anion and 1,3-dibromopropane (63%), but when 1,4-dibromobutane and bis-chloromethyl ether were allowed to react in similar conditions, the corresponding phosphonates 133 − 135 were obtained in poor yields (Scheme ) . The problem seems to lie in the relatively weak nucleophilicity and thermal instability of the difluoromethylphosphonate anion .…”
Section: 42 Synthesis Via αα-Difluoromethylphosphonate Carbanionsmentioning
confidence: 99%
“…The reported yields vary from 0% to 43% with simple primary alkyl iodides and bromides. 34,[197][198][199][200][201][202][203] A recent work brings an example of the goodyielding reaction between [( i PrO) 2 P(O)CF 2 ]anion and 1,3dibromopropane (63%), but when 1,4-dibromobutane and bis-chloromethyl ether were allowed to react in similar conditions, the corresponding phosphonates 133-135 were obtained in poor yields (Scheme 44). 204 The problem seems to lie in the relatively weak nucleophilicity and thermal instability of the difluoromethylphosphonate anion.…”
Section: Coupling With Organyl Halides and Triflatesmentioning
confidence: 99%